Flow Pattern Analysis and Performance Improvement of Regenerative Flow Pump Using Blade Geometry Modification - J. Nejadrajabali; A. Riasi; S. A. Nourbakhsh (International Journal of Rotating Machinery)
Regenerative pump is a low specific speed and rotor-dynamic turbomachine capable of developing high heads at low flow rates. In this paper, a numerical study has been carried out in order to investigate the effect of blade angle on the performance of a regenerative pump. Two groups of impellers were employed. The first type has symmetric angle blades with identical inlet/outlet angles of ±10°, ±30°, and ±50° and the second group has nonsymmetric angle blades in which the inlet angle was set to 0° and six different angles of ±10°, ±30°, and ±50° were designed for the outlet of the blades. A total of 12 impellers, as well as primary radial blades impeller, were investigated in this study. The results showed that all forward blades have higher head coefficients than radial blades impeller at design flow coefficient. It was found that regenerative pumps with symmetric angle forward blades have better performance than other types. Also, it is worth mentioning that the highest head coefficient and efficiency occur at angle +10<β<+30 of symmetric angle blades. It was found that the maximum efficiency occurs at angle of +15.5° by curve fitting to the data obtained from numerical simulations for symmetric angle forward blades.